2021
DOI: 10.12688/f1000research.27725.2
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing non-adherence to opioids in cancer patients: a mixed-methods cross-sectional study

Abstract: Background: Strong opioids are mainly utilized to attenuate pain in cancer patients. Adherence to analgesic drugs significantly promotes adequate pain management and improves quality of life. We aimed to identify the factors influencing non-adherence to strong opioids in cancer patients. Methods: A descriptive, cross-sectional, two-phased, mixed methods design was conducted prospectively to evaluate a cohort of 101 cancer patients who are currently prescribed strong opioids from a pain clinic in Thailand betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In head and neck patients the prevalence of pain is particularly high [ 89 ]. Overall, cancer pain impacts 66% of patients across all cancer types [ 90 , 91 ]. The evidence suggests that management of cancer pain is far from optimal [ 92 ].…”
Section: Informationmentioning
confidence: 99%
“…In head and neck patients the prevalence of pain is particularly high [ 89 ]. Overall, cancer pain impacts 66% of patients across all cancer types [ 90 , 91 ]. The evidence suggests that management of cancer pain is far from optimal [ 92 ].…”
Section: Informationmentioning
confidence: 99%
“…The barriers to compliance were fear of the possible long-term outcomes, concern about opioid side effects, and a poor understanding of their illness. 7 A meta-analysis by Bennett showed that educational interventions on cancer pain improve patients' knowledge of and attitudes toward pain and analgesia. It was also found that the interventions increased medication adherence, thereby minimizing pain intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, people are at risk of antimicrobial resistance (Pumtong et al, 2020 ). Importantly, irrational drug use is common in persons with chronic illnesses such as cancer (Seangrung et al, 2020 ) and diabetes mellitus (Yensabai et al, 2016 ). In addition, a high prevalence of potentially inappropriate medication use was found among older Thai persons (Jenghua et al, 2019 ; Vatcharavongvan & Puttawanchai, 2019 ).…”
mentioning
confidence: 99%